High‐Performance Near‐Infrared Harvesting Transparent Luminescent Solar Concentrators. Issue 8 (24th February 2020) - Yang, Chenchen; Moemeni, Mehdi; Bates, Matthew; Sheng, Wei; Borhan, Babak; Lunt, Richard R.
Abstract: Transparent luminescent solar concentrators (TLSCs) selectively harvest ultraviolet and near‐infrared photons. Due to the absence of electrodes, busbars, and collection grids over the solar harvesting area, the device structure enables these devices to achieve the highest levels of transparency and aesthetics. Recently, COi 8DFIC has been developed as a nonfullerene acceptor in organic photovoltaics with unprecedented performance. In this work, nonfullerene acceptors are introduced into TLSCs as the luminophores. The impact of COi 8DFIC concentration on power conversion efficiency (PCE), aesthetic quality, and scalability is systematically studied. After device optimization, the COi 8DFIC TLSCs are shown to achieve a PCE over 1.2% while the average visible transmittance exceeds 74% and color rendering index exceeds 80. This work reports the highest TLSC device efficiency at the highest visibly transparency and highlights that the photoluminescent properties of these emerging low bandgap organic molecules providing an encouraging path to higher TLSC performance. Abstract : Transparent luminescent solar concentrators (TLSCs) are demonstrated with nonfullerene acceptors as near‐infrared selective‐harvesting luminophores. Optimized devices reach a power conversion efficiency over 1.2% with an average visible transmittance of 74%, the highest TLSC device efficiency at the highest visibly transparency reported to date.